ANALISIS STRATEGI USAHA DALAM MENINGKATKAN PENDAPATAN USAHA KERIPIK PISANG TIGA BINTANG DI DESA PURWO BAKTI KABUPATEN BUNGO - Jumiati Jumiati; Usdeldi Usdeldi; Dessy Anggraini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Three Star Banana Chips is a productive economic business opportunity which is carried out by individuals or business entities in order to increase income, so that they can meet life's needs. In developing a business, there needs to be a development strategy to be able to maximize the steps in developing Three Star Banana Chips. The research results show that Three Star Banana Chips can be developed by using the 4P marketing strategy or marketing mix by prioritizing product quality, affordable prices, good and friendly word of mouth promotion and channeled to grocery stores and also minimarkets.